Reliance on natural resources, renewable energy adoption, and their impact on carbon emissions in selected SCO member countries - Anas, Muhammad; Alsabhan, Talal H.; Ali, Liaqat; Alshagri, Reem (Frontiers in Environmental Science, 2025)
The connection between natural resource use, renewable energy adoption, and achieving carbon neutrality has sparked extensive debate in recent years. In response, many countries are implementing policies aimed at transitioning to low-carbon, sustainable economies. The Shanghai Cooperation Organization (SCO), representing 42% of the global population and 25% of its landmass, wields considerable geopolitical influence. However, limited empirical studies have explored the interplay between natural resource rents, renewable energy use, and territorial CO2 emissions (TCO2) within its member states. This study employs the Method of Moments Quantile Regression (MMQR) to analyze disaggregated resource rents and renewable energy adoption effects on TCO2 across SCO nations from 2000 to 2021, addressing a critical research gap with policy-relevant insights. The results align with prior research, indicating that countries rich in natural resources generally exhibit higher CO2 emissions, primarily driven by their dependence on fossil fuels. The statistically insignificant coefficients for renewable energy across all quantiles indicate its limited and inconsistent influence on TCO2 emissions. This underscores the challenge posed by sluggish renewable adoption, particularly in oil-dependent economies, in mitigating carbon output. The continued prevalence of non-renewable energy sources remains a substantial obstacle. To overcome this challenge, it is essential for policies to focus on expediting the transition to renewable energy by investing in infrastructure, technology, and innovation. This research adds to the broader conversation on achieving a balance between energy-resource consumption and environmental sustainability.